Pengaruh Media Pembelajaran Berbasis Macromedia Flash Terhadap Kemampuan Komunikasi Matematis Siswa - Dita Yustika Septiyani; Saleh haji; Agus Susanta (Didactical Mathematics, 2022)
This study aims to analyze the effect of learning media based on Macromedia Flash on students' mathematical communication skills. This type of research is a quasi-experimental research with a quantitative approach. The population in this study were class IX students at MTs Darussalam Bengkulu City in the 2021/2022 academic year. The research sample was selected using a purposive sampling technique by taking into account the students' initial abilities. 18 students of class IX.A were chosen as the experimental class using macromedia flash-based learning media and 19 students of class IX.B were the control class with conventional learning. Data was collected through observation, tests, and questionnaires. Data analysis was carried out with the anacova test statistic. The results of this study indicate that there is an effect of learning media based on macromedia flash on students' mathematical communication skills with test results t_count=3,523>t_table=2,028. Learning using macromedia flash-based media can bridge students in communicating mathematical concepts so that they can be used by teachers in other materials.